Exposure to bisphosphonates and risk of cancer: a protocol for nested caseecontrol studies using the QResearch primary care database - Vinogradova, Yana; Coupland, Carol; Hippisley-Cox, Julia (BMJ Publishing Group, 2012)
Introduction: Bisphosphonates are becoming a common treatment for osteoporosis particularly after discovery of the association between hormone replacement therapy and increased risk of breast cancer. As osteoporosis develops with age, treatment is a long-term intervention. Randomised control trials typically have limited follow-up times, which restricts investigation of the effects of the drugs on risk of primary cancers. A few observational studies have demonstrated a reduced risk of breast cancer and possibly of endometrial cancer in bisphosphonate users. Two epidemiological studies have studied the effect of the drugs on oesophageal cancer but did not reach any definite conclusions. So far, no effects on colorectal and stomach cancer have been shown. This study will investigate the association of bisphosphonates with risks of the 10 most common primary cancers. Methods and analysis: A series of nested caseecontrol studies will be based on the general population using records from 660 UK general practices within the QResearch Database. Cases will be patients with primary cancers diagnosed between 1996 and 2011. Each case will be matched by age, sex, practice and calendar year to five controls, who are alive and registered with the practice at the time of diagnosis of the case. Exposure to bisphosphonates will be defined as at least one prescription during the study period. For the most common cancers with substantial numbers of observations, the effect of the duration of the treatment and different types of bisphosphonates will be studied. Conditional logistic regression will be applied to produce ORs adjusted for smoking status, socioeconomic status, ethnicity, cancer-specific co-morbidities and use of other medications.